Retensi Karyawan Sebagai Mediasi Dalam Pengaruh Talent Management Dan Motivasi Kerja Terhadap Kinerja Karyawan - Qonita Tillah; Pardiman Pardiman; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This research purposes to analyze the impact of Talent Management and Work Motivation on Employee Performance, with Employee Retention as a mediating variable at CV. Aneka Grafika Malang. The background of this research is the declining number of employees and decreasing performance achievement over the past three years, which have affected operational stability and production target attainment. This research employed a quantitative explanatory approach. The population consisted of 114 employees, and a saturated sampling (census) technique was applied, involving all employees as respondents. Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) was used to examine the data. The findings indicate that Talent Management has a positive and significant impact on Employee Performance. Work Motivation does not have a significant effect on Employee Performance. Talent Management and Work Motivation significantly influence Employee Retention. Employee Retention significantly affects Employee Performance. However, Employee Retention does not significantly mediate the relationship between Talent Management and Work Motivation on Employee Performance. The practical implication suggests that the company should strengthen a structured and sustainable Talent Management system to improve workforce stability and operational performance. Keywords: Talent Management,Work Motivation, Employee Retention, Employee Performance.